Development of Eco-Friendly Biocomposite Films Based on Opuntia ficus-indica Cladodes Powder Blended with Gum Arabic and Xanthan Envisaging Food Packaging Applications - Malha Oudir; Zohra Ait Mesbah; Djahida Lerari; Nadia Issad; Djamel Djenane (Foods, 2023)
Currently, food packaging is facing a critical transition period and a major challenge: it must preserve the food products’ quality and, at the same time, it must meet the current requirements of the circular economy and the fundamental principles of packaging materials eco-design. Our research presents the development of eco-friendly packaging films based on Opuntia ficus-indica cladodes (OFIC) as renewable resources. OFIC powder (OFICP)-agar, OFICP–agar-gum arabic (GA), and OFICP–agar-xanthan (XG) blend films were eco-friendlily prepared by a solution casting method. The films’ properties were investigated by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (X-RD), and differential scanning calorimeter (DSC). Water solubility and moisture content were also determined. Morphology, thickness, molecular interactions, miscibility, crystallinity, and thermal properties, were affected by adjusting the gums (GA and XG) content and glycerol in the blend films. Moisture content increased with increasing glycerol and XG content, and when 1.5 g of GA was added. Water solubility decreased when glycerol was added at 50% and increased with increasing GA and XG content. FTIR and XRD confirmed strong intermolecular interactions between the different blend film compounds, which were reflected in the shifting, appearance, and disappearance of FTIR bands and XRD peaks, indicating excellent miscibility. DSC results revealed a glass transition temperature (Tg) below room temperature for all prepared blend films, indicating that they are flexible and soft at room temperature. The results corroborated that the addition of glycerol at 30% and the GA to the OFICP increased the stability of the film, making it ideal for different food packaging applications.